In Silico Test of Active Compounds of Pomegranate Fruit (Punica granatum) Against Estrogen Receptor-α for Osteoporosis - Anandawijaya, Spica Diani; Latifah, Nurul; Latifah, Ifa; Nugraha, Primadini Ayesha (Indonesian Journal of Chemical Science, 2025)
Osteoporosis is a systemic bone disease characterized by decreased bone density, so bone breaks easily. In this study, the activity of the phytoestrogen compound content in pomegranates (Punica granatum) against estrogen alpha in Silico. The study aims to get new drug candidates for osteoporosis therapy. The method used is to dock the re-docking of the natural ligands of raloxifene and docking against the ligands of test compounds which are secondary metabolite compounds in pomegranates. The Gridbox used has coordinates x center : -2,079; y center : -30,746; z center : 22,813. The caffeic acid test compound has the best potential binding to the alpha estrogen receptor.